2018
DOI: 10.3390/f9090514
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Islands Hosting Marginal and Peripheral Forest Tree Populations: The Case of Pinus brutia Ten. in Cyprus

Abstract: Mediterranean islands have served as important Tertiary and glacial refuges, hosting important peripheral and ecologically marginal forest tree populations. These populations, presumably harboring unique gene complexes, are particularly interesting in the context of climate change. Pinus brutia Ten. is widespread in the eastern Mediterranean Basin and in Cyprus in particular it is the most common tree species. This study evaluated genetic patterns and morphoanatomical local adaptation along the species geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
4
5
0
Order By: Relevance
“…This finding is in accordance with population genetic studies of forest trees that observed high genetic diversity in the western populations of Pinus brutia (Eliades, Aravanopoulos, & Christou, 2018) and Cedrus brevifolia (Eliades, Gailing, Lenemann, Fady, & Finkeldey, 2011). This is potentially a consequence of the local topography facilitating the maintenance of higher effective population sizes in this region during the Pleistocene climatic oscillations, and/or of less intensive historical human impact (livestock grazing and logging) than in Eastern Troodos (Eliades et al, 2018). The decline of haplotypic diversity in soil microarthropod assemblages eastwards may therefore indicate incipient biodiversity loss, as genetic variation tends to be eroded more quickly than species diversity under scenarios of global change (Balint et al, 2011).…”
Section: The Utility Of Asvs For Community Ecologysupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in accordance with population genetic studies of forest trees that observed high genetic diversity in the western populations of Pinus brutia (Eliades, Aravanopoulos, & Christou, 2018) and Cedrus brevifolia (Eliades, Gailing, Lenemann, Fady, & Finkeldey, 2011). This is potentially a consequence of the local topography facilitating the maintenance of higher effective population sizes in this region during the Pleistocene climatic oscillations, and/or of less intensive historical human impact (livestock grazing and logging) than in Eastern Troodos (Eliades et al, 2018). The decline of haplotypic diversity in soil microarthropod assemblages eastwards may therefore indicate incipient biodiversity loss, as genetic variation tends to be eroded more quickly than species diversity under scenarios of global change (Balint et al, 2011).…”
Section: The Utility Of Asvs For Community Ecologysupporting
confidence: 90%
“…In contrast to OTUs, ASV richness varied significantly along a longitudinal axis with local communities harbouring more haplotypes westwards (Table 1; Figure S3), which might be interpreted as a signature of higher on average intraspecific genetic diversity in the Western part of the mountain range, which has historically been less affected by anthropogenic disturbance (Delipetrou et al, 2008). This finding is in accordance with population genetic studies of forest trees that observed high genetic diversity in the western populations of Pinus brutia (Eliades, Aravanopoulos, & Christou, 2018) and Cedrus brevifolia (Eliades, Gailing, Lenemann, Fady, & Finkeldey, 2011). This is potentially a consequence of the local topography facilitating the maintenance of higher effective population sizes in this region during the Pleistocene climatic oscillations, and/or of less intensive historical human impact (livestock grazing and logging) than in Eastern Troodos (Eliades et al, 2018).…”
Section: The Utility Of Asvs For Community Ecologysupporting
confidence: 84%
“…This result indicates that the CYP provenance has a higher degree of phenotypic plasticity than the other provenances used in this study. Eliades et al (2018) evaluated genetic and morphoanatomical diversity of P. brutia populations from Cyprus by using isoenzyme analysis and measuring morphoanatomical traits of needless and cones. The authors concluded that P. brutia growing in Cyprus is a peripheral population with high genetic and morphoanatomical diversity, despite its small geographical distribution within an island.…”
Section: Cold Hardiness Variations Among Provenancesmentioning
confidence: 99%
“…In the Western Palearctic, the Mediterranean Basin represents a region of exceptional genetic and species diversity both of flora and fauna and it is therefore recognized as a Global Biodiversity Hotspot [1][2][3][4][5]. Due to the colonization of structurally very different peninsulas (Iberian, Apennine, Balkan, and Anatolian Peninsulas), island archipelagos (of the Mediterranean Sea and Macaronesia), and the North African coastline, many species occur in marginal or isolated distributional areas with regard to their European core distributions [3,6,7]. At a more narrow spatial scale, the Mediterranean Basin comprises multiple regional vegetational Biodiversity sub-Hotspots [8][9][10] which largely coincide with several climatically stable refugia, where many endemic species have survived during the Pliocene and Pleistocene [11][12][13].…”
Section: Introductionmentioning
confidence: 99%